Persfektif Islam Tentang Kedudukan dan Peranan Guru dalam Pendidikan - Arfandi Arfandi (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
A teacher is someone who provides knowledge to their students and is responsible for educating, teaching, guiding, directing, assessing and evaluating their students so that it is useful in the future. Professional teachers are teachers who are able to apply multidimensional relationships. Such teachers are those who internally have four competencies, namely: pedagogical competence, professional competence, personality competence, and social competence. The Islamic perspective on the position and role of the teacher is to position the teacher or educator in a noble position. Educators are positioned as spiritual fathers (spiritual father) for their students. He provides spiritual food with knowledge and development of noble morals (akhlaqalkarimah) and straightens them out. To create educators who are professional as well as competent in Islamic education, it is based on the demands of the Prophet because he was the only most successful educator in a short span of time, so that it is hoped that he can get closer to the reality of the educator with the ideal (Prophet Saw). The following are the competencies of Islamic educators and education: Religious Personal Competencies, Religious Social Competencies and Religious Professional Competencies.